Corporate Social Responsibility sebagai Daya Dukung Ekonomi Baru Masyarakat Desa Sanggula Kecamatan Moramo Utara Kabupaten Konawe Selatan Studi PT. Lintas Stone Mineral - Mursin, Mursin; Zulzaman, Zulzaman; Hisna, Hisna; Hasdairta Laniampe, Hasdairta Laniampe; Salebaran, Salebaran; Said, Taufiq (Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to find out the role of CSR in supporting community welfare and the CSR program of PT. Lintas Stone Mineral. This study uses Resource-Based View (RBV) Theory, the method used in this study is Ethnographic research with a qualitative approach with data collection using observation techniques and in-depth interviews (interviews) of data analyzed in a qualitative descriptive way. The result of this study is the Role of Corporate Social Responsibility of PT. Lintas Stone Mineral in supporting the economic welfare of the community includes empowering the local community, CSR plays an important role in helping to support the economy of the community affected by the company as part of the company's social responsibility, in addition to that through this CSR program can create new fields for the people of Sanggula Village so that this is expected to be able to suppress the occurrence of economic inequality in the community. PT Lintas Stone Mineral's Corporate Social Responsibility program provided by the company is assistance in catfish nurseries, laying hens, super free-range chickens, MSME assistance, and plant seed assistance. So that this can be expected and used as a new economic source for the community Keywords: CSR, Economic Welfare, Sanggula Community.